Injuries and rapid weight loss in elite adolescent taekwondo athletes: A Korean prospective cohort study - Kim, CW.; Park, K. J. (Physikalische Medizin - Rehabilitationsmedizin - Kurortmedizin, 2020)
Objectives: To report injury patterns associated with training activities of elite adolescent Taekwondo athletes who are expected to represent South Korea in the future.